"Othering" and "Self-othering" in the Book of Tobit: A Jungian approach - Efthimiadis-Keith, Helen (HTS teologiese studies, 2018)
The Book of Tobit is replete with various instances of ‘othering’ that hold the potential for alienation and a variety of strong emotions. For example, Tobit ‘others’ Anna by insisting that she had stolen a goat, whereas she had not. Following a Jungian paradigm, this paper reads the various ‘otherings’ inherent in the interrelationships between the characters as reflections of the main character’s relationship with himself. In so doing, it analyses these relationships through Jung’s concepts of Eros/Logos and anima/animus to determine the nature of Tobit’s ‘self-othering’ and its effect on those around him. It is concluded, among others, that Tobit’s multiple ‘self-otherings’ and his ‘othering’ of ‘other’ characters are because of his suppression of his anima-Eros function that has, in turn, given rise to a dominant (and demonic) animus-Logos.